Faktor- Faktor Yang Mempengaruhi Kepuasan Nasabah Bank Negara Indonesia Kcp Sei Panas Kota Batam - Monica Chester Breemer; David Humala Sitorus (Economics and Digital Business Review, 2024)
The level of customer satisfaction is determined by the quality of the products and services they expect, so quality assurance is the main thing for a company. In achieving customer satisfaction with services, there are two main things that are closely related, namely customer expectations of service quality and consumer perceptions of service quality. The aim of this research is to determine and analyze the partial and simultaneous influence of service, trust and product excellence on customer satisfaction at Bank Negara Indonesia KCP Sei Panas Batam City. The type of research used is quantitative research, this data collection uses questionnaires to 300 customers who frequently carry out transactions at the company. In this research, the variables of service, trust and product excellence have an influence of 83.5% and 16.5% are influenced by variables outside this research. The results of this research show that service has a positive and significant effect on customer satisfaction, trust has a positive and significant effect on customer satisfaction and excellence has a positive and significant effect on customer satisfaction.